Japanese Semiaspectual Forms -teshimau and -teoku as Discourse Markers - Rachmat, Nandang; Otsuka, Hiroko (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
This paper discusses the Japanese semi aspectual forms -teshimauÂ and -teokuÂ function as discourse markers which serve as speakerâ€™s intentions of utterances for rapport management. In general, the semantic function of the morphological semi aspectual forms such asÂ -teshimauÂ and -teokuÂ are explained as expressions of feelings of remorse or regret as well as preparatory actions, respectively. Both of them derived from the explanation of â€œcompletionâ€ as a core meaning. The meanings mentioned above are also learned in elementary and pre-intermediate levels of Japanese language learning as a second language. However, the results of this research, which derived from analysis using I-JAS corpus dialogue data, indicate that in interpersonal discourse, these aspectual forms are used to show self-deprecating and modest attitudes, sentimental mood, or inevitable and difficult situations. Additionally, as a discourse marker, they are used to express utterance intentions such as showing speakerâ€™s responsible recognition for the situation occurred, respecting the opinion of the interlocutor, and avoiding current topic to be continued. They also function as act of politeness due to the effects of â€œdown gradersâ€ and â€œupgradersâ€ in Spencer-Oatey's theory of rapport management, while in this research indicates that improperly use of -teokuÂ might sound impolite depending on the utterance situations. Furthermore, it was found that they work as discourse markers for rounding up dialogs or shifting topics, and there are differences between -teshimauÂ and -teokuÂ in whether it is the interlocutorâ€™s topic or the speakerâ€™s topic that was being rounded up. For these reasons, second language acquisition requires learning about indicative meanings of these forms that function in the contexts and utterance situations, and the findings of this research will also contribute to the research of Japanese language teaching materials.